The paediatric iron deficiency assessment with reticulocyte haemoglobin equivalent (Ret-He) in comparison with biochemical markers of serum ferritin and transferrin saturation - Nurasyikin Yusof; Ho, SLC; Rabeya Y; Hafiza Alauddin; Suria Abdul Aziz (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Diagnosis of iron deficiency anaemia (IDA) is a challenge as the conventional methods often diagnose the disease at the later stage. Haemoglobin content of reticulocytes is useful to identify IDA at earlier stage. The objective of this study was to evaluate reticulocyte-haemoglobin equivalent (Ret-He) in diagnosing IDA in children and to compare it with other conventional methods. This prospective study was conducted on 120 paediatric patients aged 12 years and below, who attended Hospital Sultanah Aminah Johor Bahru, Malaysia with haemoglobin <12 g/dL. Ret-He and serum iron, ferritin and transferrin saturation were measured. Using a cut-off point of 20% for transferrin saturation, 81 out of 120 subjects (67.5%) were found as iron deficient. Based on the diagnosis of IDA, cut-off value for Ret-He using the Receiver Operating Characteristics (ROC) curve analysis was found as 22.65 pg. Ret-He showed a good sensitivity and specificity of 77.8% and 66.7%, respectively. As compared with Ret-He, serum ferritin showed a sensitivity of only 18.9%. However, a good specificity of 100% suggest it is useful for ruling in the disease but not suitable for screening. Transferrin saturation showed a good sensitivity and specificity, but it is biologically variable and not cost effective as a screening tool. Correlation study showed serum iron and transferrin saturation have significant positive correlation with Ret-He (r=0.415 to 0.518). However, there was no correlation between Ret-He and serum ferritin (r=0.051, p=0.578). This study shows that Ret-He at a cut-off point of 22.65 pg has a better sensitivity and potentially be useful as a screening tool in the paediatric population.